Erich Mühsams Tanthologie: ein literarisches Plädoyer gegen die Erbschaftspraxis im deutschen Kaiserreich - Junginger, Carl (Internationales Archiv für Sozialgeschichte der deutschen Literatur, 2024)
At first glance, Erich Mühsam’s Psychologie der Erbtante . Eine Tanthologie aus 25 Einzeldarstellungen als Beitrag zur Lösung der Unsterblichkeits-Frage (1905) seems to be apolitical and entertaining literature, ridiculing childless and husbandless Rich Aunts (Erbtanten). But as I show in a close-reading analysis, Mühsams uses this wildly known stereotype to target the bourgeois kinship and inheritance continuities of his time. The ongoing inheritance tax debates at the turn of the century provide the necessary socio-historical context to understand the satirical implications on which - so my overall hypothesis runs - both the comedy of the text and its socio-political explosiveness are based.
Gesehen am 10.02.2025